Security Analysis of QAM Quantum-Noise Randomized Cipher System - Yukai Chen; Haisong Jiao; Hua Zhou; Jilin Zheng; Tao Pu (IEEE Photonics Journal, 2020)
Applying the quadrature amplitude modulation (QAM) format, quantum-noise randomized cipher (QNRC) systems hide the signal states in quantum phase noise and amplitude noise to prevent eavesdropping. In this paper, based on the traditional wire-tap channel model analysis method, the physical-layer security of QAM-QNRC system is investigated quantitatively under the metric of secrecy rate. The general expressions of secrecy rates of the data and key are derived separately. Furthermore, the maximum reachable secrecy rate of a QAM-QNRC system is put forward, under which the data and key are both safe in the view of mutual information evaluation. Finally, the variation trend of secrecy rate with various system parameters is discussed in detail. The simulation results show that we can obtain a higher secrecy rate by setting reasonable parameters, such as the level of ciphertext, mesoscopic signal power, and inner gain at the transmitter. Meanwhile, the security of the key is the main constraint of the maximum reachable secrecy rate.